GREEN HUMAN RESOURCE MANAGEMENT DAN GREEN ENGAGEMENT CLIMATE UNTUK MENINGKATKAN GREEN INNOVATIVE WORK BEHAVIOR KARYAWAN SARUNG TENUN ATBM UD AL–ARIF DI GRESIK - Haidar, Mohammad Ali; Amiartuti Kusmaningtyas (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research aims to identify the influence of Green Human Resource Management and Green Engagement Climate to improve Green Innovative Work Behavior at UD. Al-Arif in Gresik. The sample in this research was 87 employees using a saturated sample. This research uses Social Exchange Theory, and this type of research uses quantitative methods. This research uses simple linear regression analysis, while for mediation testing using the Sobel test, and for hypothesis testing using the t test. The results of the analysis findings from this research can be concluded as follows, 1) Green human resource management influences the green engagement climate of UD ATBM woven sarong employees. AL-ARIF in Gresik, 2) Green human resource management influences the green innovative work behavior of UD ATBM woven sarong employees. AL-ARIF in Gresik, 3) Green engagement climate influences green innovative work behavior of UD ATBM woven sarong employees. AL-ARIF in Gresik, 4) Green human resource management influences green innovative work behavior through the green engagement climate of UD ATBM woven sarong employees. AL-ARIF in Gresik. Keywords: Green Human Resource Management, Green Innovative Work Behavior and Green Engagement Climate.